Practical pricing and the airline industry - Poelt, Stefan (Henry Stewart Talks, 2009)
Introduction and basics of pricing and revenue management, Demand and no-show forecasting, Evolutions of optimization methods from static optimization (EMSR) over dynamic optimization to network optimization, Practical aspects of forecasting and optimization, Overbooking methods and performance measurement, Recent and future revenue management developments, The pricing process and interactions of pricing and revenue management